Strategi Pemasaran Konten Melalui Media Sosial Instagram Di Bali Coconut House - Ni Wayan Chintia Pinaria; Ade Ruly Sumartini (UNHI Press, 2023)
In the current era, companies are required to be able to manage their content on social media in a professional manner. High-quality content can increase engagement with customers. Content marketing is a marketing approach that involves creating, curating, distributing, and amplifying content that is engaging, relevant, and useful to audiences. Bali Coconut House is one of the homestays in Taro Tourism Village, Tegalalang, Gianyar. This homestay uses social media Instagram in marketing its products. The purpose of this research is to find out the right content marketing strategy through Instagram social media at Bali Coconut House. The research location was carried out at the Bali Coconut House. This study uses a qualitative research approach. The informant in this study is the owner of the Bali Coconut House. Data collection techniques using interview and observation methods. The content marketing strategy through Instagram social media at Bali Coconut House can be carried out by implementing 8 elements, namely setting goals, classifying consumers, planning content, creating content, distributing content, strengthening content, evaluating the content, and developing content. The suggestions that can be conveyed in this research are that in planning content for Bali Coconut House, it is better to have a content calendar, collaborate with attractions in the Taro tourism village and utilize information on Instagram Insight.